2015
DOI: 10.1002/anie.201509711
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Diazo Compounds with Difluorocarbene: An Efficient Approach towards 1,1‐Difluoroolefins

Abstract: A transition-metal-free difluoromethylenation of diazo compounds that proceeds under mild conditions has been developed and is based on the use of TMSCF2 Br as the difluoromethylene source and tetrabutylammonium bromide (TBAB) as the promoter. The chemoselective formal carbene dimerization reaction is achieved owing to the electronic properties and the relative stability of the difluorocarbene intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(50 citation statements)
references
References 69 publications
0
49
0
1
Order By: Relevance
“…However, these traditional methods that apply carbonyl groups as a precursor to gem ‐difluoro olefines are limited in application due to strongly basic reaction conditions and limitations in the substrate scope . More recently, difluorocarbene was found to be an efficient precursor to synthesize gem ‐difluoro olefins from aryldiazoacetates (Scheme b) . There are few examples on the application of fluorinated diazoalkanes as a precursor of a CF 2 moiety, although recently, Wang and co‐workers reported the gem ‐difluorovinylation of organoboronic acids with 2,2,2‐trifluoro diazoethane following elimination of HF under strongly basic and forcing conditions at elevated temperature (100 °C) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these traditional methods that apply carbonyl groups as a precursor to gem ‐difluoro olefines are limited in application due to strongly basic reaction conditions and limitations in the substrate scope . More recently, difluorocarbene was found to be an efficient precursor to synthesize gem ‐difluoro olefins from aryldiazoacetates (Scheme b) . There are few examples on the application of fluorinated diazoalkanes as a precursor of a CF 2 moiety, although recently, Wang and co‐workers reported the gem ‐difluorovinylation of organoboronic acids with 2,2,2‐trifluoro diazoethane following elimination of HF under strongly basic and forcing conditions at elevated temperature (100 °C) …”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] More recently, difluorocarbene was found to be an efficient precursor to synthesize gem-difluoro olefins from aryldiazoacetates (Scheme 1 b). [9][10][11] There are few examples on the application of fluorinated diazoalkanes as a precursor of a CF 2 moiety, although recently, Wang and coworkers reported the gem-difluorovinylation of organoboronic acids with 2,2,2-trifluoro diazoethane following elimination of HF under strongly basic and forcing conditions at elevated temperature (100 8C). [12] Intrigued by these findings, we envisioned the introduction of a (2,2-difluorovinyl)-benzene group onto indole heterocycles [13] and electron-rich aromatic systems through carbene transfer of fluorinated diazoalkanes under mild reaction conditions (Scheme 1 c).…”
Section: Synthesis Of Gem-difluoro Olefins Through C à H Functionalizmentioning
confidence: 99%
“…[7] How-ever,asurvey of the literature indicates that difluoroketene is quite unstable and it facilely undergoes decomposition to generate CO and difluorocarbene. [8] In view of the fact that carbonylation of Fischertype carbenes with CO is as traightforward method for generating ketene, [9,10] we have hypothesized that difluoroketene may be generated directly from CO and difluorocarbene, which has recently attracted attention as at ype of electrophilic carbene [11,12] (Scheme 1b). [8] In view of the fact that carbonylation of Fischertype carbenes with CO is as traightforward method for generating ketene, [9,10] we have hypothesized that difluoroketene may be generated directly from CO and difluorocarbene, which has recently attracted attention as at ype of electrophilic carbene [11,12] (Scheme 1b).…”
mentioning
confidence: 99%
“…[7a] In 2004, Bergman et al reported an iridium-stabilized difluoroketene,w hich provided the only structural information for difluoroketene in any form. [8] In view of the fact that carbonylation of Fischertype carbenes with CO is as traightforward method for generating ketene, [9,10] we have hypothesized that difluoroketene may be generated directly from CO and difluorocarbene, which has recently attracted attention as at ype of electrophilic carbene [11,12] (Scheme 1b). However,s ome initial efforts based on this hypothesis proved to be futile.T he expected a,a-difluoro-b-lactam was not observed.…”
mentioning
confidence: 99%